The knowledge of acute stroke management and its associated factors among healthcare providers in Emergency Department, Hospital USM - Omar, Rosniza (2019)
Introduction Current evidence showed a huge gap between evidences and practice on acute stroke treatment, which subsequently translated into the low rate of intravenous (IV) thrombolysis usage. As a gatekeeper in initial management for acute ischemic stroke (AIS) patients, healthcare provider at emergency department (ED) need to have sufficient knowledge in order to improve the rate of IV thrombolysis. The aims of the study were to explore the level of knowledge on AIS management, as well as its associated factors for better usage of IV thrombolysis in the future. Materials and Methods This study was a cross-sectional study from February 2018 until April 2018 at ED Hospital Universiti Sains Malaysia (HUSM). A validated questionnaire was distributed among the healthcare providers during the study period. The questionnaire included respondent’s sociodemographic data, experience and knowledge management. Results A total of 120 participants included in the study. There were more females than males, either staff nurses, (46 (38.3%)) or postgraduate medical doctors, (45 (37.5%)). The mean (67 (55.8%)), with a mean age of 31.2 (3.82) years old. Most of the participants were either staff nurses, (46 (38.3%)) or postgraduate medical doctors, (45 (37.5%)). The mean score for the knowledge was highest among the service medical officers with mean score of 25.5 (5.19), followed by postgraduate medical doctors’ group with mean score of 25.4 (4.22). Only 26.7% of participants have no experience in usage of rTPA in stroke (mean=20.22 (6.71)) have higher score in knowledge compared to those who had clinical experience less than 5 years (mean=16.17 (8.2)) with -4.05 mean difference (95%CI: - 6.96, -1.14). There were significant mean difference compared by occupations where doctors are more knowledgeable. Conclusion Most healthcare provider have better level of knowledge in pre-hospital and ED stroke management compare to the knowledge of eligibility criteria for IV thrombolysis. Many of them have interest in stroke management and had experienced in the use of rTPA in stroke thrombolysis. Occupation of doctors and clinical working experience are associated with higher level of knowledge and may improve the management of AIS patients.